A smart wearable posture correcting device based on spine curvature and vibration measurement - Christhudass, Jerome; Perumal, Manimegalai; Balachandran, Kowsalya; Chella Muthu, Sella Dharshini; Balasubramanian, Keerthana (Institute of Advanced Engineering and Science, 2025)
In the United States, aalmost 50 billion is expended in neck pain therapy each year. Poor posture, which affects the primary tendon responsible for reproducing finished tasks on time, has previously been recognized as a major source of upper spine discomfort. The primary objective of this study is to design and develop a device that not only detects deviations in posture but also employs vibration alerts to encourage corrective actions. The methodology involves the integration of an inertial measurement unit (IMU) sensor and a Flex Sensor to measure the angle and position of the spine, enabling real-time posture assessment. Additionally, a Piezo-electric sensor is incorporated to measure the vibration of the user's spine. The device provides real-time feedback via a mobile application to help users maintain optimal posture. Data analysis involved filtering and machine learning-based classification to assess posture deviations. The system demonstrated an accuracy of 90% in classifying posture states, with an average error of 2.7° in spine curvature measurement. This research contributes to the field of wearable technology by offering an innovative solution for posture correction, emphasizing the importance of proactive interventions in fostering healthy habits.